Efektivitas Program Pelayanan Jemput Bola dalam Meningkatkan Kepemilikan Akta Kelahiran pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Timor Tengah Utara - Yosephine Agustin Helly; Ajis Salim Adang Djaha; Rouwland Alberto Benyamin; Petrus Kase (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Birth certificate ownership is a fundamental right of every citizen and an essential requirement for accessing various public services. However, the coverage of birth certificate ownership in North Central Timor Regency has not yet reached the national target. To address this issue, the Department of Population and Civil Registration of North Central Timor Regency implemented the Mobile Service Program (Jemput Bola) as an initiative to bring civil registration services closer to the community. This study aims to analyze the effectiveness of the Mobile Service Program in increasing birth certificate ownership in North Central Timor Regency. The research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The analysis of program effectiveness was based on Richard M. Steers’ goal approach and strategic constituencies approach. The findings indicate that the Mobile Service Program is effective in expanding service accessibility, increasing the number of birth certificates issued, and facilitating public access to civil registration documents. The program also received positive responses from the community because it reduced barriers related to cost, time, and distance in obtaining birth certificates. Nevertheless, several challenges remain, including low public awareness, incomplete administrative requirements, limited internet connectivity, and geographical constraints. Therefore, strengthening public outreach, improving coordination with village governments, and establishing measurable program targets are necessary to enhance the program’s effectiveness in a sustainable manner.